Comprehensive Modulation of Secondary Metabolites in Terpenoid-Accumulating Mentha spicata L. via UV Radiation - Gaia Crestani; Kristýna Večeřová; Natalie Cunningham; Uthman O. Badmus; Otmar Urban; Marcel A. K. Jansen (Plants, 2024)
In plants, secondary metabolites change in response to environmental conditions. These changes co-regulate resilience to stressful environmental conditions, plant growth and development, and interactions between plants and the wider ecosystem, while also affecting soil carbon storage and atmospheric and climatic conditions. The objective of this study was to determine the association between UV exposure and the contents of key metabolites, including amino acids, phenolics, flavonoids, terpenoids, carotenoids, tocopherols, and phytosterols. Mentha spicata plantlets were grown in tissue culture boxes for 30 days and then exposed to a low dose of broadband UV-B (291–315 nm; 2.8 kJm−2 biologically effective UV) enriched light for eight days. Metabolite contents were quantified either immediately after the final UV exposure, or after seven days of recovery under photosynthetically active radiation. It was found that UV promoted the production of flavonoids (1.8-fold) ahead of phenolic acids (unchanged). Furthermore, the majority of monoterpenes and sesquiterpenes, constituents of valuable mint essential oil, were significantly increased through UV treatment (up to 90-fold for α-linalool). In contrast, the contents of carotenoids and tocopherols did not increase following UV exposure. A comparison between plants sampled immediately after UV exposure and after seven days of recovery showed that there was an overall increase in the content of carotenoids, mono- and sesquiterpenes, phenolics, and amino acids following recovery, while the contents of sterols and tocopherols decreased. These UV-induced changes in metabolite profile may have important consequences for agriculture, ecology, and even the global climate, and they also provide an exciting opportunity to enhance crop value, facilitating the development of improved products with higher levels of essential oils and added benefits of enhanced flavour, colour, and bioactive content.